An enhanced 17-level hybridized multilevel inverter with stair case modulation - Hemalatha Javvaji; Basavaraja Banakara (Institute of Advanced Engineering and Science, 2020)
This paper proposes a Hybridized Symmetric Cascaded Multilevel Inverter for voltage levels ranging from 5 levels to 17 levels. The proposed Multi Level Inverter (MLI) topology is built using a modified H-bridge inverter that results in an increased output voltage levels with a smaller number of solid-state switches. This technique enhances the h-bridge configuration from three level to five level by means of a bi-directional switch at source. Gating pulses of hybridized symmetric MLI are generated through staircase modulation. The operation and performance of the proposed topology is tested for different output voltage levels, simulation results prove that the proposed technique results in less THD at all levels with lesser power consumption and are easily applicable for renewable energy applications.